A Load Balancing Policy for Distributed Web Service - Eludiora, Safiriyu Ijiyemi; Aderounmu, Ganiyu A.; Abiona, Olatunde; Oluwatope, Ayodeji; Onime, Clement E.; Kehinde, L. O. (Scientific Research, 2023)
3(08):645-654 · January 2010